1990
DOI: 10.1080/02640419008732148
|View full text |Cite
|
Sign up to set email alerts
|

Postural consistency in skilled archers

Abstract: The consistency of an archer's postural set at the moment of loose (arrow release) is commonly perceived to be an important determinant of success. The coach seeks, among other things, to provide the archer with information about postural consistency, details of which he acquires by eye or occasionally by video-recordings. The gains that might be achieved from more precise information are examined here. Nine skilled archers, classified into either skilled or elite groups according to their officially computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 16 publications
0
32
0
2
Order By: Relevance
“…The task used in this study emulates the dynamics of aiming and releasing motions of the aiming and release motions in archery; hence, the findings of this study would provide valuable insights into understanding the kinetics and control of multi-digits in archery. Previous studies have reported that the most important determinant of archery performance is the finger movement in the release phase (Hah & Yi, 2008;Stuart & Atha, 1990). The DOF of the fingers may influence force control, which varies throughout the short release phase, viewing the relationship between the problem regarding the DOF of the fingers and the game performance from biomechanical and motor control perspectives would enable a broad understanding of successful shooting motion in archery.…”
Section: Discussionmentioning
confidence: 99%
“…The task used in this study emulates the dynamics of aiming and releasing motions of the aiming and release motions in archery; hence, the findings of this study would provide valuable insights into understanding the kinetics and control of multi-digits in archery. Previous studies have reported that the most important determinant of archery performance is the finger movement in the release phase (Hah & Yi, 2008;Stuart & Atha, 1990). The DOF of the fingers may influence force control, which varies throughout the short release phase, viewing the relationship between the problem regarding the DOF of the fingers and the game performance from biomechanical and motor control perspectives would enable a broad understanding of successful shooting motion in archery.…”
Section: Discussionmentioning
confidence: 99%
“…Each participant shot a total of 36 arrows. Finally, we collected a total of 144 data sets from the four participants (n = 4) (considering references [1,3]). …”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, the first researchers to pay attention to postural consistency were Stuart and Atha. In their study [1], Stuart and Atha used a three-dimensional optoelectronic scanner to measure the positions of the archer's head and elbow and that of the bow at the moment of "loose" (releasing the arrow). Postural consistency is defined as the consistency in the archer's positioning that is within-ends the standard deviation (SD) of the positions for each archer.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Stuart and Atha (1990) Objective: The aim of this study was to investigate the relationship between aiming patterns and scores in archery shooting.…”
Section: Introductionmentioning
confidence: 99%
“…especially for motion analysis in the field of sports science.A study by Stuart and Atha (1990) Objective: The aim of this study was to investigate the relationship between aiming patterns and scores in archery shooting.,Method: Four (N = 4) elementary-level archers from middle school participated in this study. Aiming pattern was defined by averaged acceleration data measured from accelerometers attached on the body during the aiming phase in archery shooting.…”
mentioning
confidence: 99%